PENGEMBANGAN WEBSITE FUKU ELEKTRONIK SEBAGAI MEDIA PEMASARAN SECARA DIGITAL - Lina, Ph.D.; Ferbian Loekman; Michelle Augustine (Jurnal Bakti Masyarakat Indonesia, 2022)
Fuku Elektronik is an online electronics store that has been established since 2019, located in the West Jakarta area. Until now, Fuku Elektronik store operates by selling through accepting the arrival of buyers at the store, as well as selling through online media marketplaces. Along with technological developments, e-commerce has become a more efficient sales medium in the digital era. Not only that, entrepreneurs will also find it easier to market their products or services. This technological development has made Fuku Elektronik interested in marketing its products so that they can be known more widely through e-commerce applications. Previously, Fuku Elektronik had marketed its products by placing paid advertisements on the Tokopedia, Shopee, and other well-known marketplaces. However, Fuku Elektronik does not yet have its own website to provide product information, display testimonials, or make sales. The Pengabdian Kepada Masyarakat (PKM) team has designed and developed a website for Fuku Elektronik and conducted website usage training for the store staffs. In addition, it is hoped that with the existence of the Fuku Elektronik website, it will be easier for buyers to interact directly with Fuku Elektronik. The developed website is also used as a promotional medium for Fuku Elektronik store. Fuku Elektronik's website development applies the implementation method from the Software Development Life Cycle (SDLC) stage which starts with planning using the waterfall model method, analysis of time, costs, and resources, designing wireframes, testing the developed system, and implementing the system. The output of this PKM activity is a website for Fuku Elektronik as a media to bring Fuku Elektronik's products or services closer to buyers. The developed website has been used by Fuku Elektronik as a means of promoting their business ABSTRAK: Fuku Elektronik merupakan toko elektronik online yang berdiri sejak 2019 yang berlokasi di daerah Jakarta Barat. Hingga saat ini toko Fuku Elektronik beroperasi dengan melakukan penjualan secara fisik dengan menerima kedatangan pembeli pada toko, maupun penjualan melalui media marketplace secara online. Seiring dengan perkembangan teknologi, e-commerce telah menjadi media penjualan yang lebih efisien di era digital. Tidak hanya itu, para pengusaha juga akan dengan lebih mudah memasarkan produk atau jasanya. Perkembangan teknologi ini membuat Buku Elektronik tertarik untuk memasarkan produknya sehingga dapat dikenal lebih luas melalui aplikasi e-commerce. Sebelumnya, Fuku Elektronik telah memasarkan produknya melalui pemasangan iklan berbayar di aplikasi Tokopedia, Shopee, dan market place ternama lainnya. Namun Fuku Elektronik belum memiliki website tersendiri untuk memberikan informasi produk, menampilkan testimoni, maupun melakukan penjualan. Tim pelaksana pengabdian kepada masyarakat (PKM) telah melakukan perancangan dan pengembangan website bagi Fuku Elektronik dan melakukan pelatihan penggunaan website kepada para staf toko Fuku Elektronik. Selain itu, diharapkan dengan keberadaan website Fuku Elektronik maka pembeli akan dimudahkan saat ingin berinteraksi langsung dengan toko Buku Elektronik. Website yang dikembangkan juga digunakan sebagai media promosi toko Fuku Elektronik. Pengembangan website Fuku Elektronik menerapkan metode pelaksanaan dari tahapan Software Development Life Cycle (SDLC) yang dimulai dari perencanaan dengan metode waterfall model, analisis terhadap waktu, biaya, dan sumber daya, perancangan wireframe, pengujian sistem yang dikembangkan, serta implementasi sistem. Produk yang dihasilkan dalam kegiatan PKM ini adalah website untuk e-commerce Fuku Elektronik sebagai sarana yang lebih mendekatkan produk atau jasa Fuku Elektronik kepada pembeli. Hasil website yang dihasilkan telah digunakan oleh Fuku Elektronik sebagai sarana promosi usaha mereka.